Recent advances in nanoformulations for co-delivery of curcumin and chemotherapeutic drugs - Maryam Hashemi; Mahboubeh Ebrahimian (Nanomedicine Journal, 2017)
The application of chemotherapy in cancer treatment has been limited due to cause side effects such as toxicity against normal cells and drug resistance. In recent years, numerous studies have been focused on using natural products with chemotherapeutic drugs to enhance therapeutic efficiency and reduce cytotoxicity. On the other hand, encapsulation of drugs into nanoparticles (NPs) can improve solubility of hydrophobic drug; circulation time in blood and the residence at the pathological site by enhance permeation and retention (EPR) effect. It has been shown that curcumin (CUR) has  wide range of pharmacological activities against many diseases such as cancer. CUR has been demonstrated to be a potent chemosensitizer that can induce additive or synergistic effects with chemotherapeutic drugs against different cancer cell lines.  Recently, various types of nanocarriers have been investigated for CUR.  In this review, different co-formulations containing Cur and chemotherapeutic drugs used in cancer therapy are discussed with emphasis on their pharmaceutical properties.